2009
DOI: 10.1021/tx800289z
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption of Ultrafine Metal Oxide and Its Influence on Cytotoxicity toward Cultured Cells

Abstract: Many investigations about the cellular response by metal oxide nanoparticles in vitro have been reported. However, the influence of the adsorption ability of metal oxide nanoparticles toward cells is unknown. The aim of this study is to understand the influence of adsorption by metal oxide nanoparticles on the cell viability in vitro. The adsorption abilities of six kinds of metal oxide nanoparticles, namely, NiO, ZnO, TiO2, CeO2, SiO2, and Fe2O3, to Dulbecco's modified Eagle's medium supplemented with a 10% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
189
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(206 citation statements)
references
References 42 publications
15
189
1
1
Order By: Relevance
“…While the concentrations used in this study were relatively high, they are comparable to those used in previous nanotoxicity studies (0.5-5 mg/mL) utilising A549 cells [8,9,35,36]. In [35], for example, the viability of A549 cells was found to significantly decrease (580% relative to the control group), following incubation with 7 nm TiO 2 NPs at concentrations greater than 5 mg/mL. Similarly, Kim et al [36] observed a 20% decrease in colony numbers (viability) after the A549 cells were exposed to 0.5 mg/mL of 20-40 nm TiO 2 or 20 nm Al 2 O 3 NPs for 10 days, as measured by the clonogenic assay.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…While the concentrations used in this study were relatively high, they are comparable to those used in previous nanotoxicity studies (0.5-5 mg/mL) utilising A549 cells [8,9,35,36]. In [35], for example, the viability of A549 cells was found to significantly decrease (580% relative to the control group), following incubation with 7 nm TiO 2 NPs at concentrations greater than 5 mg/mL. Similarly, Kim et al [36] observed a 20% decrease in colony numbers (viability) after the A549 cells were exposed to 0.5 mg/mL of 20-40 nm TiO 2 or 20 nm Al 2 O 3 NPs for 10 days, as measured by the clonogenic assay.…”
Section: Discussionsupporting
confidence: 62%
“…Horie et al [35] concluded that the adsorption of medium components (e.g. serum proteins and Ca 2ĂŸ ) must be taken into account when evaluating the cytotoxicity of low-toxicity materials like TiO 2 .…”
Section: Impact Of Np Supernatants On Cell Proliferationmentioning
confidence: 99%
“…For instance, Horie et al 35 have described relationships between physico-chemical NP properties and the biological responses they evoke. They suggested a five step in vitro !…”
Section: The Role Of Physico-chemical Np Properties In the Interactiomentioning
confidence: 99%
“…However, examples of in vitro tests using human cells showed gaps in the understanding of parameters that control ZnO behavior, dissolution and hence toxicity. Especially under physiological conditions, the ZnO behavior, mainly its dissolution, is influenced by constituents of the cell culture media [15,16]. With respect to surface charge and zeta potential and their influence on the toxicity, several hypotheses have been proposed [4,11,14].…”
Section: Introductionmentioning
confidence: 99%